Small business : critical perspectives on business and management. Volume I (New York : Routledge, 2000)
This volume presents Critical Perspectives on Business and Management of Small Business about: Births and Deaths.
Keywords: Business; Enterprises; Entrepreneurship; Small business; Entrepreneurship; Small business; New business enterprises; Self-employed.